2009
DOI: 10.1021/jp902501v
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical Capture of Carbon Dioxide on Lithium Aluminates (LiAlO2 and Li5AlO4): A New Option for the CO2 Absorption

Abstract: Lithium aluminates (LiAlO(2) and Li(5)AlO(4)) were synthesized, characterized, and tested as possible CO(2) captors. LiAlO(2) did not seem to have good qualities for the CO(2) absorption. On the contrary, Li(5)AlO(4) showed excellent behavior as a possible CO(2) captor. Li(5)AlO(4) was thermally analyzed under a CO(2) flux dynamically and isothermically at different temperatures. These results clearly showed that Li(5)AlO(4) is able to absorb CO(2) in a wide temperature range (200-700 degrees C). Nevertheless,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
107
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(123 citation statements)
references
References 26 publications
14
107
1
Order By: Relevance
“…Experiments on Li 2 CO 3 at temperatures up to 973 K showed coupling between the rate of Li ionic motion and that of carbonate ion rotation, and the presence of a faster regime with faster Li ionic motion that is only activated at high temperatures. 11 This regime matches well with the second rapid regime of CO 2 absorption seen in similar materials such as Li 5 AlO 4 and Li 2 CuO 2 , [12][13][14] and indicates that the rate of gas absorption may be linked to the rate of ionic transport in the bulk material.…”
Section: Introductionsupporting
confidence: 76%
“…Experiments on Li 2 CO 3 at temperatures up to 973 K showed coupling between the rate of Li ionic motion and that of carbonate ion rotation, and the presence of a faster regime with faster Li ionic motion that is only activated at high temperatures. 11 This regime matches well with the second rapid regime of CO 2 absorption seen in similar materials such as Li 5 AlO 4 and Li 2 CuO 2 , [12][13][14] and indicates that the rate of gas absorption may be linked to the rate of ionic transport in the bulk material.…”
Section: Introductionsupporting
confidence: 76%
“…The sorption of carbon dioxide by lithium containing the metal oxides was studied at a temperature between 400 and 700 °C (Pfeiffer et al 2007;Korake and Gaikwad 2011). Equilibrium and kinetics of CO 2 sorption by lithium zirconate were explored at a temperature range from 400 to 700 °C (Gupta and Fan 2002;Kalinkin et al 2003;Ida and Lin 2003;Nakagawa et al 2003;Pfeiffer and Bosch 2005;Khomane et al 2006;Mosqueda et al 2006;Yi and Eriksen 2006;Avalos-Rendon et al 2009;Iwan et al 2009;;Fauth et al 2004;Wang and Lee 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The extracted alkaline-earth metal from silicate waste material, steelmaking slag and waste concrete could be used for the CO 2 mineral sequestration process by adjusting the pH swing in an acidic condition (Kodama et al 2008). An earlier study reported the preparation of calcium silicate hydrate (CSH) solids using hydrated lime and iron blast furnace slag in an aqueous agitated slurry at 92 °C (Brodnax and Rochelle 2000). A synthetic adsorbent crystalline CSH was used to remove endotoxin (Zhang et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the theoretical CO 2 chemisorption capacities (mmol of CO 2 per gram of ceramic) for the most studied alkaline and alkaline-earth ceramics. As it can be seen, metal oxides (Li 2 O, MgO and CaO) are among the materials with the best CO 2 capture capacities. Nevertheless, Li 2 O and MgO have not been really considered as possible options due to reactivity and kinetics factors, respectively.…”
Section: Co 2 Capture By Different Alkaline and Alkaline-earth Ceramicsmentioning
confidence: 95%
“…Among the alkaline and/or alkaline-earth oxides, various lithium, sodium, potassium, calcium and magnesium ceramics have been proposed for CO 2 capture through adsorption and chemisorption processes [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. These materials can be classified into two large groups: dense and porous ceramics.…”
Section: Co 2 Capture By Different Alkaline and Alkaline-earth Ceramicsmentioning
confidence: 99%